Factors Influencing the Program Decision-Making for College Degree as Perceived by Grade 12 HUMSS Student at Bestlink College of the Philippines: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Choosing a college degree is one of the most important life decisions a student can make. This study aimed to determine the factors influencing the program decision-making for college degrees as perceived by Grade 12 HUMSS students in Bestlink College of the Philippines. This study will help many confused and undecided students, especially those graduating senior high school. The researchers used the Qualitative method and Descriptive research design for this study. A Google Forms questionnaire is used to gather the necessary data for this research. A random sampling technique is conducted in choosing the respondents. The study revealed that different factors affect the graduating senior high school from choosing their respective courses. Internal factors such as their talents and abilities and external factors such as family and friends greatly influence the program decision-making for the graduating senior high school college degree.
Keywords: decision-making; college course; HUMSS; BCP